2021
DOI: 10.1101/gad.345454.120
|View full text |Cite
|
Sign up to set email alerts
|

RAD21 is a driver of chromosome 8 gain in Ewing sarcoma to mitigate replication stress

Abstract: Aneuploidy, defined as whole-chromosome gain or loss, causes cellular stress but, paradoxically, is a frequent occurrence in cancers. Here, we investigate why ∼50% of Ewing sarcomas, driven by the EWS-FLI1 fusion oncogene, harbor chromosome 8 gains. Expression of the EWS-FLI1 fusion in primary cells causes replication stress that can result in cellular senescence. Using an evolution approach, we show that trisomy 8 mitigates EWS-FLI1-induced replication stress through gain of a copy of RAD21. Low-level ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 56 publications
(76 reference statements)
4
41
0
Order By: Relevance
“…EWS/FLI has been reported to increase basal transcription in Ewing sarcoma cells resulting in R loop formation ( Gorthi et al., 2018 ). Unresolved R loops can also lead to stalled/collapsed replication forks, DNA damage, and replicative stress in non-transformed primary cells ( Su et al., 2021 ). It is possible that increased R loops and replicative stress are, in part, responsible for the DNA damage phenotype observed with further upregulated EWS/FLI expression by TRIM8 inhibition, the subject of future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…EWS/FLI has been reported to increase basal transcription in Ewing sarcoma cells resulting in R loop formation ( Gorthi et al., 2018 ). Unresolved R loops can also lead to stalled/collapsed replication forks, DNA damage, and replicative stress in non-transformed primary cells ( Su et al., 2021 ). It is possible that increased R loops and replicative stress are, in part, responsible for the DNA damage phenotype observed with further upregulated EWS/FLI expression by TRIM8 inhibition, the subject of future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation and function of cohesin may be tissue-specific, and mutations in cohesin are more prominent in certain types of tumors [37]. Recent advances in bladder cancer, colorectal cancer, breast cancer, hepatocellular carcinoma, prostate cancer, and Ewing sarcoma studies have demonstrated that cohesin subunits play a pivotal role in the genesis and development of human tumors [38][39][40][41][42][43]. However, few studies have focused on the significance of cohesin subunits in ESCA.…”
Section: Discussionmentioning
confidence: 99%
“…By keeping sister chromatids more tightly paired, cohesin could facilitate template switching to repair DNA lesions and promote efficient fork restart [ 47 , 87 ]. In line with such a model, increased expression of the cohesin subunit RAD21 mitigates replication stress in Ewing sarcoma cells [ 176 ]. In addition, cohesin may contribute to promote fork protection and homologous recombination (HR) by the PDS5-dependent recruitment of BRCA2 and RAD51 to stalled replication forks ( Figure 3 B) [ 173 , 177 , 178 ].…”
Section: The Cohesin Complex and Associated Factors In The Dna Replication Stress Responsementioning
confidence: 95%